Assessment of the Use of the Potential of Agricultural Lands in Voronezh Region - V Shishkina, Natalia; E Yushkova, Victoriya; A Mamistova, Ekaterina (KnE Life Sciences, 2019)
The uniqueness and specifics of the land significantly affects both the organization of agricultural production and the rural area management. In order to make well-founded management decisions the economic subjects and public authorities need scientific grounding for assessment of land potential and its use efficiency. The authors suggest using three approaches to land quality and use assessment: agro-climatic potential, land quality score and agricultural production per hectare. Uniting these approaches into single assessment procedure produces a fairly objectively estimation of the economic potential of agricultural land in each selected territory.